From theory to practice: reflections on teacher education through Supervised Internship and Pedagogical Residency - Botelho, Laura Silveira; Dias, Marcella Fernanda Gomes (Debates em Educação, 2026)
The objective of this research is to investigate the contributions and challenges of the Curricular Supervised Internship (CSI), and the Pedagogical Residency (PR), in the teacher training of students from the undergraduate programs in Portuguese Language and Pedagogy. To this end, we analyze the perceptions of students regarding these modalities, highlighting their influence on the integration of theory and practice, as well as the construction of their teaching identity. The theoretical framework is based on research on Teacher Education in the Brazilian context (Gatti, 2010, 2019; Nóvoa, 2017; Pimenta, 2012; Pimenta & Lima, 2004). The adopted methodology is qualitative and interpretivist, with data being generated through the application of a structured questionnaire using Google Forms. The results reveal a significant comparison between the Curricular Supervised Internship and the Pedagogical Residency, highlighting significant nuances in their formative approaches. The CSI is often described as observational, with limited opportunities for teaching and practical application,according to the student-teachers. In contrast, the PR stands out for its integration of theory and practice, allowing greater involvement in planning, teaching practice, and continuous feedback, providing more comprehensive and immersive experiences. However, challenges persist, such as the limitation in the number of slots and scholarships, as well as bureaucratic demands. Despite their differences, both modalities are seen as fundamental spaces for teacher education, contributing to the understanding of school realities and the challenges of the profession.